Analysis of Foot-Ankle Coordination, Agility, and Self-Confidence Towards The Ball-Drifting Skills Of Extra-Curricular Students of SMP Negeri 1 Binamu - Ramadhan, Reynaldi; Hudain, Muh. Adnan; Yasriuddin, Yasriuddin; Usman, Arifuddin; Syahruddin, Syahruddin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This type of research is path analysis, The subjects of this study were extracurricular students of SMP Negeri 1 Binamu, totalling 30 male students. Data analysis using SPSS 30.00 using descriptive tests, normality tests and hypothesis tests. It is known that there is a direct effect of Foot-Eye Coordination (X1) on Self-Confidence (X3) in extracurricular football students of SMP Negeri 1 Binamu, based on the results of the analysis obtained in the table shows that the coefficient value ß is -0.313 with a calculated -0.800 and significance (p) = 0.067 (p <0.05); (2) There is a direct effect of Agility (X2) on Self-Confidence (X3) in extracurricular football students of SMP Negeri 1 Binamu, based on the results of the analysis obtained in the table shows that the coefficient value ß is -0.718 with a calculated T of -0.455 and significance (p) = 0.785 (p <0.05); (3) There is a direct influence of foot-eye coordination (X1) on dribbling skills (Y) in extracurricular football students at SMP Negeri 1 Binamu, based on the analysis results obtained in the table showing that the coefficient value ß is 0.126 with a T count of 1.911 and significance (p) = 0.067 (p < 0.05); (4) There is a direct influence of agility (X2) on dribbling skills (Y) in extracurricular football students at SMP Negeri 1 Binamu, based on the analysis results obtained in the table showing that the coefficient value ß is 0.073 with a T count of 0.276 and significance (p) = 0.785 (p < 0.05); (5) There is a direct influence of Self-Confidence (X3) on Dribbling Skills (Y) in extracurricular football students of SMP Negeri 1 Binamu, based on the analysis results obtained in the table showing that the coefficient value of ß is 0.033 with T count 1.025 and significance (p) = 0.315 (p < 0.05); (6) There is no influence of Foot-Eye Coordination (X1) through Self-Confidence (X3) on Dribbling Skills (Y) in extracurricular football students of SMP Negeri 1 Binamu with a beta coefficient value of -0.313 (0.126 > -0.225); (7) There is no influence of Agility (X2) through Self-Confidence (X3) on Dribbling Skills (Y) in extracurricular football students of SMP Negeri 1 Binamu, with a beta coefficient value of -0.799 (0.073 > -0.718)